Litispendência entre as demandas coletivas - Caldeira, Adriano Cesar Braz (2008)
This essay has as purpose a legal institution that is subject of frequent controversies amongst law scholars and case law, to wit, lis pendens between collective actions, and between the latter and individual ones. In spite of the existence of excellent works mentioned in the bibliography hereof on lis pendens among such kinds of actions, they are very limited as regards individual actions. We understood that dealing with collective action complying with merely and strictly those rules applicable to individual lawsuits is a mistake, with all due respect. This paper aims at analyzing which are those actions that may be considered as collective indeed. Thus, Civil Public Action, Popular Action, Collective Mandamus, Collective Injunction Order, Direct Unconstitutionality Action, Action for Declaration of Constitutionality, Argumentation of a Basic Principle Breach, Action against Dishonesty in Administration. This paper carries out a preliminary analysis of issues like legitimacy, the very concept of party, the internal formation of lawsuits (parties, claim, and cause of action), the effects resulting from the decision, so that the main issue may be eventually dealt with. It is concluded that there are two criteria of setting lis pendens between those institutions: one of them, traditional, characterized whenever the same internal elements of a lawsuit are present; another, that takes into account the claim s identity, although some internal elements may be different. This thesis points out further contrarily from what is observed in lis pendens for individual actions that in collective actions the lawsuit should not be dismissed, but rather gathered together, by virtue of a possible higher extent thereof, as it can occur with the cause of action, and as a way of preventing the other action s holder s free access to the Judiciary